Capacitação em comunicação interpessoal para enfermeiros gerentes de uma instituição pública de saúde - Risso, Amanda Creste Martins da Costa Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Introduction: The managerial functions pointed out as a nurse’s responsibilities (providing care/assisting, managing/administrating, researching and teaching) allow for envisaging ways to understand more clearly that “managing” is a tool in the work “caregiving” process. Among the many skills that a nurse manager must have and develop, the main ones are: decision-making, leadership, continuing education, management/administration and communication. In the function of a nursing manager, communication takes place from the interactions established by the nurse when performing some common activities, such as developing and providing orientation about norms, routines, and procedures; evaluating the nursing-team collaborators’ performance; writing memoranda and official letters; drawing up work and holiday schedules; and so many other ways of getting in tune with people by means of face-to-face, written, spoken and computerized messages. Objective: To propose and implement a Verbal and Non-verbal Interpersonal Communication Training Program for the nurse managers at a public health care institution based on the theoretical framework of interpersonal communication. Method: This is a qualitative study developed at a public health care institution in São Paulo state involving fifteen nurse managers working in hospitalization units who accepted to participate in the study voluntarily after approval by the Research Ethics Committee under CAAE number 23057113.2.0000.5411. Data collection was performed by means of three semi-structured interviews, the first of which was conducted in the pre-training period (M1), and the following ones applied in the post-training phase (M2 and M3). The training on interpersonal communication took place during four meetings on the nurses’ work site, based on a previously structured program. The Content Analysis methodological framework, according to Bardin, was used for data analysis in light of the theoretical frameworks of Interpersonal Communication, the Management Theories and the Teaching and Human Learning Theory. Results: The participants in the study were between 27 and 54 years old; they had been working as nurse managers at the institution for 2 months to 23 years, and all of them were females. During the pre-training period, two categories emerged. The organization of the communication concept is based on common sense under the influence of everyday activities in the nurse’s managerial work, and the recognition of the communication variables in the management process is related to the nurses’ professional experiences. After the conduction of the Training Program, the emerging categories were: construction of the verbal and non-verbal interpersonal communication competence in the management process; comprehension of the potentialities and fragilities of interpersonal communication in management processes; and developing awareness of the need for continuing and expanded learning about the communication formation process. Concluding remarks: The nurse managers stated that the training enabled their perception of the importance of effective communication in managerial processes because it consisted in a fundamental tool to be applied in the professional and personal realms, as it enables conscious, consistent and clear actions in management processes. The training meetings promoted social integration, with the opportunity of exchanging valuable experiences, for both the participants and the researcher, thus enriching the moments spent together and providing significant learning. The suggestions provided showed the involvement of participants as regards their desire for changes in management communication processes to be implemented in the various scenarios of the institution where they work.

Introdução: As funções apontadas como responsabilidade do enfermeiro (cuidar/assistir, gerenciar/administrar, pesquisar e ensinar) permitem vislumbrar caminhos para compreender com maior clareza que “gerenciar” é uma ferramenta do processo de trabalho “cuidar”. Dentre as inúmeras competências que o enfermeiro gerente deve ter e desenvolver, as principais são: tomada de decisão, liderança, educação permanente, gerenciamento/administração e comunicação. Na função de gerente em enfermagem, a comunicação ocorre a partir das interações estabelecidas pelo enfermeiro ao desempenhar algumas atividades comumente desenvolvidas como elaboração e orientação com relação a normas, rotinas, e procedimentos, avaliação de desempenho de colaboradores da equipe de enfermagem, redação de memorandos e ofícios, elaboração das escalas de trabalho e de férias, e tantas outras formas de pôr-se em sintonia com as pessoas por meio de mensagem face a face, escritas, faladas e informatizadas. Objetivo: Propor e implementar um Programa de Capacitação em Comunicação Interpessoal Verbal e Não Verbal baseado no referencial teórico da comunicação interpessoal aos enfermeiros gerentes de uma instituição pública de saúde. Método: É um estudo qualitativo, desenvolvido em uma instituição pública de saúde do Estado de São Paulo com quinze enfermeiros gerentes que atuam em unidades de internação hospitalar que aceitaram participar voluntariamente do estudo após aprovação do Comitê de Ética em Pesquisa sob o n. CAAE 23057113.2.0000.5411. A coleta de dados foi realizada por meio de três entrevistas semiestruturadas, sendo a primeira na pré-capacitação (M1) e as seguintes, pós-capacitação (M2 e M3). A capacitação em comunicação interpessoal aconteceu em quatro encontros de acordo com o programa previamente estruturado e no ambiente de trabalho. Na análise dos dados foi utilizado o referencial metodológico de Análise de Conteúdo de Bardin, à luz dos referenciais teóricos da Comunicação Interpessoal, das Teorias da Administração e da Teoria de Ensino e Aprendizagem Humana. Resultados: Os participantes do estudo tinham idade entre 27 e 54 anos; tempo de atuação profissional como enfermeiro gerente na instituição entre 2 meses e 23 anos e, todos eram do sexo feminino. Na pré-capacitação surgiram duas categorias: A estruturação do conceito de comunicação está baseada no senso comum sob influência do cotidiano do trabalho gerencial do enfermeiro e, O reconhecimento das variáveis comunicativas no processo de gestão está relacionado com as experiências profissionais dos enfermeiros e, após a realização do Programa de Capacitação, as categorias emergentes foram: Construção da competência em comunicação interpessoal verbal e não verbal no processo de gestão, Compreensão das potencialidades e fragilidades da comunicação interpessoal nos processos de gestão, e, Conscientização da necessidade da aprendizagem contínua e ampliada do processo de formação da competência comunicacional. Considerações finais: Os enfermeiros gerentes afirmaram que a capacitação permitiu a percepção da importância da comunicação efetiva nos processos gerenciais, constituindo uma ferramenta fundamental a ser aplicada no âmbito profissional e pessoal, pois possibilita, nos processos de gestão, ações conscientes, consistentes e providas de clareza. Os encontros da capacitação promoveram interação social, com oportunidade de intercâmbio de experiências valiosas, tanto para os participantes quanto para a pesquisadora, enriquecendo os momentos de convívio e favorecendo a aprendizagem significativa. As sugestões fornecidas evidenciaram o envolvimento dos participantes no que se refere ao desejo de transformações dos processos comunicacionais na gestão a serem implantados nos diversos cenários da instituição em que trabalham
Training on interpersonal communication for nurse managers at a public health institution
Keywords: Enfermagem; Comunicação; Administração; Recursos humanos